(untitled) (Zaporizhzhia Historical Review, 2021)
Basing on the published and non-published primary sources, the article describes the problem questions of administrative system and territorial configuration of ´Freedoms of Zaporozhzhian Cossack Hostª in 1734ñ 1775.